Conjugated Polyelectrolyte/Bacteria Living Composites in Carbon Paper for Biocurrent Generation. Issue 16 (3rd February 2022) - Vázquez, Ricardo Javier; McCuskey, Samantha R.; Quek, Glenn; Su, Yude; Llanes, Luana; Hinks, Jamie; Bazan, Guillermo C.
Abstract: Successful practical implementation of bioelectrochemical systems (BES) requires developing affordable electrode structures that promote efficient electrical communication with microbes. Recent efforts have centered on immobilizing bacteria with organic semiconducting polymers on electrodes via electrochemical methods. This approach creates a fixed biocomposite that takes advantage of the increased electrode's electroactive surface area (EASA). Here, it is demonstrated that a biocomposite comprising the water‐soluble conjugated polyelectrolyte CPE‐K and electrogenic Shewanella oneidensis MR‐1 can self‐assemble with carbon paper electrodes, thereby increasing its biocurrent extraction by ≈6‐fold over control biofilms. A ≈1.5‐fold increment in biocurrent extraction is obtained for the biocomposite on carbon paper relative to the biocurrent extracted from gold‐coated counterparts. Electrochemical characterization revealed that the biocomposite stabilized with the carbon paper more quickly than atop flat gold electrodes. Cross‐sectional images show that the biocomposite infiltrates inhomogeneously into the porous carbon structure. Despite an incomplete penetration, the biocomposite can take advantage of the large EASA of the electrode via long‐range electron transport. These results show that previous success on gold electrode platforms can be improved when using more commercially viable and easily manipulated electrode materials. Abstract : Schematic representation of a biocomposite comprising the conjugated polyelectrolyte CPE‐K and Shewanella oneidensis MR‐1. This environment generates more biocurrent compared to using gold electrodes.